Three Different Types of β-Glucans Enhance Cognition: The Role of the Gut-Brain Axis - Hu, Minmin; Zhang, Peng; Wang, Ruiqi; Zhou, Menglu; Pang, Ning; Cui, Xiaoying; Ge, Xing; Liu, Xiaomei; Huang, Xu-Feng; Yu, Yinghua (Frontiers in Nutrition, 2022)
Background Dietary fiber is fermented in the lower gastrointestinal tract, potentially impacting the microbial ecosystem and thus may improve elements of cognition and brain function via the gut-brain axis. β-glucans, soluble dietary fiber, have different macrostructures and may exhibit different effects on the gut-brain axis. This study aimed to compare the effects of β-glucans from mushroom, curdlan and oats bran, representing β-(1,3)/(1,6)-glucan, β-(1,3)-glucan or β-(1,3)/(1,4)-glucan, on cognition and the gut-brain axis. Methods C57BL/6J mice were fed with either control diet or diets supplemented with β-glucans from mushroom, curdlan and oats bran for 15 weeks. The cognitive functions were evaluated by using the temporal order memory and Y-maze tests. The parameters of the gut-brain axis were examined, including the synaptic proteins and ultrastructure and microglia status in the hippocampus and prefrontal cortex (PFC), as well as colonic immune response and mucus thickness and gut microbiota profiles. Results All three supplementations with β-glucans enhanced the temporal order recognition memory. Brain-derived neurotrophic factor (BDNF) and the post-synaptic protein 95 (PSD95) increased in the PFC. Furthermore, mushroom β-glucan significantly increased the post-synaptic thickness of synaptic ultrastructure in the PFC whilst the other two β-glucans had no significant effect. Three β-glucan supplementations decreased the microglia number in the PFC and hippocampus, and affected complement C3 and cytokines expression differentially. In the colon, every β-glucan supplementation increased the number of CD206 positive cells and promoted the expression of IL-10 and reduced IL-6 and TNF-α expression. The correlation analysis highlights that degree of cognitive behavior improved by β-glucan supplementations was significantly associated with microglia status in the hippocampus and PFC and the number of colonic M2 macrophages. In addition, only β-glucan from oat bran altered gut microbiota and enhanced intestinal mucus. Conclusions We firstly demonstrated long-term supplementation of β-glucans enhanced recognition memory. Comparing the effects of β-glucans on the gut-brain axis, we found that β-glucans with different molecular structures exhibit differentia actions on synapses, inflammation in the brain and gut, and gut microbiota. This study may shed light on how to select appropriate β-glucans as supplementation for the prevention of cognitive deficit or improving immune function clinically.